Fuzzy PI Controllers Performance on Boost Converter - Wakhyu Dwiono (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Electric voltage of about 220 volts is required to supply the home appliance in Indonesia, such as for lighting lamps. When there is no 220 volts power supply, while the available voltage source is equal to the battery voltage of about 1.5 to 12 volts, it requires the voltage converter to convert a low voltage 220 volts Become. By using a transformer, it is easy to rise the AC voltage. Meanwhile for DC voltage, the transformer can not be used to raise it, Because The changing magnetic field do not occur then the output of transformer voltage is not higher but the transformer Become hot Because of DC voltage. To raise the DC voltage, DC to DC converter is needed, such as Boost Converter. Boost Converter works based on the changing current that flows through an inductor. This current change will Affect the inductor voltage change. The output voltage of boost converter has a unique comparison to the input voltage duty cycle. By adjusting the amount of the voltage duty cycle, the output voltage will be easy to control. In this paper, we presented a prototype of 12 to 220 V DC-DC boost converter, using fuzzy-PI intervention that being embedded on ATmega168 AVR microcontroller. The controller can maintain a fixed output voltage by regulating the input duty cycle. From the test results, is obtained an efficiency of 75% at 15 watts whereas percentage of error of about less than 3%.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2262